2023
DOI: 10.25077/jrk.v14i1.574
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Proses Hidrolisis Rumput Laut Ulva Reticulata dengan Pelarut HNO3 untuk Produksi Bioetanol

Abstract: One alternative to make biofuels and replace petroleum-based fuels is to convert non-food ingredients from Ulva reticulata seaweed into bioethanol. Seventy percent of the earth's surface is covered by microalgae and seaweeds that can be converted into bioethanol. Ulva seaweed contains 50.3% carbohydrates in the form of heteropolysaccharides  such as glucose, arabinose, rhamnose and xylose. Optimization of the seaweed hydrolysis catalyzed by HNO3 using Microwave irradiation was done by varying acid concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Research by Kolo et al (2022) also reported that the hydrolysis of Ulva reticulata macroalga through variations in temperature and reaction time using H2SO4 catalyst obtained a sugar content of 27.79 g/L and a bioethanol content of 7.76% (9). Furthermore, research by Kolo et al (2023) reported that hydrolysis of Ulva reticulata using the HNO3 catalyst obtained a sugar content of 86.5 g/L and a bioethanol content of 37.2% (10). The three previous studies that used the macroalga Ulva reticulata had not optimized the fermentation process, so the researchers tried to optimize the fermentation process to increase bioethanol levels.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Research by Kolo et al (2022) also reported that the hydrolysis of Ulva reticulata macroalga through variations in temperature and reaction time using H2SO4 catalyst obtained a sugar content of 27.79 g/L and a bioethanol content of 7.76% (9). Furthermore, research by Kolo et al (2023) reported that hydrolysis of Ulva reticulata using the HNO3 catalyst obtained a sugar content of 86.5 g/L and a bioethanol content of 37.2% (10). The three previous studies that used the macroalga Ulva reticulata had not optimized the fermentation process, so the researchers tried to optimize the fermentation process to increase bioethanol levels.…”
Section: Introductionmentioning
confidence: 93%
“…The results of the qualitative test showed that there was a color change from orange to bluish green in both standard ethanol and fermented samples. According to Kolo et al, (2023), stated that a positive test for the presence of ethanol was indicated by a change in the color of potassium dichromate from orange to bluish green. So, it can be concluded that in the fermented sample there has been a change in glucose to ethanol, which is marked by a change in the color of the potassium dichromate solution from orange to bluish green when the fermented sample is added (10).…”
Section: Ulva Reticulata Powder Hydrolysate Fermentationmentioning
confidence: 99%